Problematika Kewarganegaraan dalam Perkawinan Beda Agama : Perspektif Hukum Nasional dan Hak Asasi Manusia - Evelyn Hatiku; Syifa Hauna Nur Syahidah; Muhammad Oriza Pradana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the complex issue of citizenship in interfaith marriages within Indonesia’s legal and human rights framework. The problem arises from the absence of explicit provisions in national law regarding the civil registration and citizenship consequences of marriages between individuals of different religions. This legal ambiguity often results in unequal recognition, difficulties in registering children’s citizenship, and broader implications for the right to identity. The research aims to analyze how Indonesian marriage law, administrative population law, and judicial interpretations interact with international and constitutional human rights principles. Using a normative juridical method combined with case study analysis and doctrinal review, this study identifies legal inconsistencies between national regulations and the principle of non-discrimination guaranteed under human rights law. The findings indicate that judicial practices, such as post-SEMA No. 2 of 2023 rulings, show a gradual shift toward balancing legal certainty with human rights protection, although disparities persist across jurisdictions. The study concludes that reform is required to clarify the status of interfaith marriages and to protect the citizenship rights of all parties involved, including children. It recommends that legislators harmonize marriage and citizenship laws with constitutional mandates and human rights instruments to ensure equality before the law, legal certainty, and respect for individual freedoms.